A study on the cultural and behavioral patterns of foreign foodies on the perception of Filipino carinderia food - Santos, Julio Lorenzo N.
This study will delve into how food enthusiasts or so called "foodies", both Filipino and foreign, perceive Filipino cuisine in this modern culinary era here in the Philippines specifically the Filipino carinderia. It will use three theories namely Theory of Cultural Determinism, Determinants of Food (EUFIC), and, the Theory of Planned Behavior as its backbone. With the use of interviews through surveys, the study aims to evaluate the relationship of external factors known as determinants between predicted behavior on Filipino Food to its consumers specifically the food enthusiasts, and, to shed light on the history and psyche behind the perception of Filipino Food relative to other cuisines, particularly its Asian neighbors.